Evaluasi Proses Bisnis Layanan Identitas Penduduk Menggunakan Quality Evaluation Framework (QEF) (Studi Kasus: Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bekasi) - Aulia Dwi Fitriani; Buce Trias Hanggara; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Bekasi Regency Population and Civil Registration Office accommodates several services in community identity documents under their tendance resident identity section. The section serves three services namely, recording electronic KTP, issuing resident identity certificates, and issuing electronic KTP. However, the service business process often inconsistencies with organizational targets so that evaluation is necessary. The stages begin with modeling a business process using the Business Process Model and Notation (BPMN), then using the Quality Evaluation Framework (QEF) method to determine which activities are experiencing mismatches. After that, problems with non-conforming activities will be identified using the Failure Mode Effect Analysis (FMEA) method so can be identified which activity need to be the main concern through the Risk Priority Number (RPN) value. Furthermore, fishbone analysis is used to determine the root of the problem. The results showed the quality factors the mismatch of the number of electronic ID card recording application files that enter to be served by the admissions counter officer (Throughput) with RPN 120 had root causes from the aspects of the machine and technology category, measurement, and method. Meanwhile, the quality factor the reception counter clerk checks the completeness of the application file (time to access) with RPN 36 has the root of the problem from the aspects of the category of machinery and technology and materials.